Long-term oncological outcomes following completely minimally invasive esophagectomy versus open esophagectomy. Issue 6 (16th January 2020) - Patel, K; Askari, A; Moorthy, K
Summary: Open esophagectomy (OE) for esophageal and gastroesophageal junctional cancers is associated with high morbidity. Completely minimally invasive esophagectomy (CMIE) techniques have evolved over the last two decades and significantly reduce surgical trauma compared to open surgery. Despite this, long-term oncological outcomes following CMIE compared to OE remain unclear. This systematic review and meta-analysis aimed to compare overall 5-year survival (OFS) and disease-free 5-year survival (DFFS) between CMIE and OE. It was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A comprehensive electronic literature search from MEDLINE, EMBASE, Web of Science, Scopus and the Cochrane Central Register of Controlled Trials was conducted. The PROSPERO database was also searched for studies comparing OFS and DFFS between CMIE and OE. The Newcastle Ottawa Scale was used to assess study quality for included studies. Overall, seven studies (containing 949 patients: 527 OE and 422 CMIE) were identified from screening. On pooled meta-analysis, there was no significant difference in OFS or DFFS between CMIE and OE cohorts ([odds ratio 1.12; 95% CI: 0.85 to 1.48; P  = 0.41] and [odds ratio 1.34; 95% CI: 0.81–2.22; P  = 0.25] respectively). Sensitivity and subgroup analysis with high-quality studies, three highest sample sized studies, and three most recent studies also revealed no difference in long-term oncological outcomes between the two operative groups. This review demonstrates long-term oncological outcomes following CMIE appear equivalent to OE based on amalgamation of existing published literature. Limited high-level evidence comparing OFS and DFFS between CMIE and OE exists. Further research with a randomized controlled trial is required to clinically validate these findings.